Living in the Bubble of Privilege : Sociological Imagination of Japanese Elite Youth from the Stories of Exchange Students in Finland - Matsui, Hinako (My University, 2023)
This thesis explores the sociological imagination of Japanese young elites from a generational perspective. Through interviews with eight Japanese exchange students in Finland, the study investigates elite students’ stressful lives by examining their aspiration for Finnish society as hints that mirrors their desire. Participants expressed the challenge of meeting Japan's social expectations and the rigid shukatsu system. The research delves into the political ignorance of these elites, attributing it to both their privileged status and extremely busy lives as highly educated university students. The study also discusses the insulating effect of their privileged backgrounds that limits their ability to understand personal challenges in a broader socio-political context. This examination emphasizes the need to critically assess the societal structures influencing the sociological imagination of Japanese young elites and the potential consequences of their political disengagement for the future of Japanese society.
Keywords: Japan, youth, generation, sociological imagination, political attitude